Analysis of algorithms to solve the discrete logarithm problem - Sim, Ernest Zi-En (Nanyang Technological University, 2024)
This project aims to explore and understand the concepts of the discrete logarithm problem. Discrete logarithm is a fundamental concept in modern cryptography. The project aims to provide an understanding of the real-world applications employed using discrete logarithm and the various methods used to solving it.